2014
DOI: 10.1016/j.nicl.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain gray and white matter changes in perinatally HIV-infected adolescents

Abstract: Despite the success of antiretroviral therapy (ART), perinatally infected HIV remains a major health problem worldwide. Although advance neuroimaging studies have investigated structural brain changes in HIV-infected adults, regional gray matter (GM) and white matter (WM) volume changes have not been reported in perinatally HIV-infected adolescents and young adults. In this cross-sectional study, we investigated regional GM and WM changes in 16 HIV-infected youths receiving ART (age 17.0 ± 2.9 years) compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 47 publications
(38 reference statements)
8
72
1
Order By: Relevance
“…It is possible that higher MD, observed in PHIV youth and HIV+ adults [20], may represent neurodegeneration of WM: where a loss in neurons during neurodegeneration, corresponds to increased water molecules, possibly resulting in higher MD [46]. Supporting this hypothesis, smaller WM volumes have been observed among PHIV youth [32]. Adults with Hepatitis C virus (HCV) infection also exhibit lower FA and higher MD compared to healthy controls [47], suggesting that different types of chronic peripheral infections and inflammation may result in similar profiles of WM microstructure abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that higher MD, observed in PHIV youth and HIV+ adults [20], may represent neurodegeneration of WM: where a loss in neurons during neurodegeneration, corresponds to increased water molecules, possibly resulting in higher MD [46]. Supporting this hypothesis, smaller WM volumes have been observed among PHIV youth [32]. Adults with Hepatitis C virus (HCV) infection also exhibit lower FA and higher MD compared to healthy controls [47], suggesting that different types of chronic peripheral infections and inflammation may result in similar profiles of WM microstructure abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of HIV on WM microstructure may possibly differ in youth with PHIV, compared to those who acquired HIV in adulthood, given that HIV exposure and cART occur when significant brain development is occurring. Sarma and colleagues [32] examined volume of WM in PHIV youth and identified WM atrophy that differed from those observed with adult-acquired HIV. To our knowledge, no study to date has utilized tractography to examine associations between disease severity markers and microstructural properties at specific points along WM tracts among PHIV youth.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a voxel-based morphometry study reported WM atrophy in the posterior part of corpus callosum, external capsule, and ventral temporal lobe in vertically infected youths (age range, 13-25 years). 13 Hoare et al 14 found that vertically HIV-infected children (age range, 8 -12 years) had lower FA and higher MD and radial diffusivity (RD) in the corpus callosum and increased MD in the superior longitudinal fasciculus. Taken together, these findings suggest that abnormal WM integrity may also be present in adolescents (age range, 12-18 years) with vertically transmitted HIV infections.…”
mentioning
confidence: 99%
“…To avoid focus bias, the use o f statistical parametric mapping (SPM), extensively used in brain research (13,22,32), enabled us to perform a compre hensive curve analysis during the whole prelanding and post landing phase. …”
mentioning
confidence: 99%